ANALISIS TEKS BAHASA INDONESIA: WACANA KRITIS DALAM WAWANCARA “PERLUASAN AKSES POLITIK KELAS MENENGAH” BENNY HANDOKO DI GREEN RADIO 89,2 FM - Hasian Romadon Tanjung (Institut Pendidikan Tapanuli Selatan, 2021)
Freedom of speech allows one to convey statements to the public. For example, the opinion and appreciation of a person about the political case facing the Indonesian nation today is likely to be self-interest or group. The research was expected to know the views of Benny Handoko about the expansion of middle-class political access in Indonesia. The method of research is qualitative and the object is the discourse. Critical discourse analysis was used to know the truth in the discourse based on the facts delivered, position of social actors, position of ideas, and events placed in the text. Data was collected by analyzing discourse critically based on existing theory. The source of research data is the discourse of the interview